Physical activity and aging research: A bibliometric analysis - Müller, A.M.; Ansari, P.; Ale Ebrahim, N.; Khoo, S. (Human Kinetics Journals, 2015)
Physical activity and aging research has burgeoned in the past few decades. Despite the increase in scholarly publications no attempts have been made to summarize the publication landscape and to identify works that had great impact to physical activity and aging research. We conducted a bibliometric analysis and collected publication data from 1980 to February 6, 2015 in the Web of Science Core Collection. Of the overall 9,935 publications most were published after 2007 and almost 60% were in the category of Geriatrics and Gerontology or Sport Sciences. Highly cited publications (n = 45) were mostly authored by researchers from US institutions and were quantitative in nature. Publications that reported on the associations or effects of physical activity on health in older adults made up 60% of the highly cited publications. We expect more scholars from various backgrounds and geographical regions to join the conversation on physical activity and aging.